Vergonha, sacrifício e testemunho: 3 desmedidas para 3 romances de J. M. Coetzee - Oliveira, Carlos Augusto Lima de (2016)
This study has as its starting point an articulation between literary discourse and testimonial speech, from the propositions of Giorgio Agamben about the idea of testimony as an Auctor speech, one who is authorized by others to report certain events. This idea of testimony differs from common sense, as something that testifies truthfully and objectively the events, but is much closer to the speech of the invention, where its veracity, and its ethical dimension, achieve what it lacks or even exceeds, reminding the Portuguese critic Silvina Rodrigues Lopes. Thus, this study is interested in analyzing three novels of the South African writer J.M. Coetzee (Waiting for the Barbarians, The Iron Age and Disgrace) as testimonials clippings of changes that spend their narrators, both inside the South African context as in other dimensions symbolized there. A testimony where slips the burden of Shame, such as an ethical manifestation’ power, in that it points out the failure of models so far established (colonialism, Apartheid, the Western civilization project), and a sacrificial order where such narrators-witnesses dive. Sacrifice of white bodies, hitherto immune, legally protected, sacralized. Sacrifice as profanation.